Pengaruh Pemberian Terapi Cairan Oral terhadap Suhu Tubuh pada Pasien Anak dengan Febris Akibat DHF - Mita Rahmawati; Indra Tri Astuti; Nopi Nur Khasanah (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease that can cause serious complications due to dehydration and plasma leakage, affecting the body temperature of patients. This study aims to examine the effect of oral fluid therapy on body temperature in pediatric patients with febrile DHF at RSU Comal Baru Pemalang. This study used a quasi-experimental design with a pretest-posttest and control group, involving 30 respondents (15 intervention and 15 control) selected through consecutive sampling based on inclusion and exclusion criteria. Body temperature data were measured using a thermometer before and after the oral fluid therapy, then analyzed using the Wilcoxon Signed Rank Test, Paired t-test, Independent t-test, and Mann-Whitney U Test with a significance level of p<0.05. The results showed that the initial body temperature of both groups was comparable (38.08°C in the intervention group and 38.13°C in the control group; p=0.739). After oral fluid therapy, the body temperature of the intervention group significantly decreased to 36.39°C, while the control group only decreased to 37.56°C, with statistical tests showing a significant difference (p<0.001). This study concludes that oral fluid therapy is effective in reducing body temperature in pediatric patients with DHF and can be recommended as part of supportive nursing management.